Manifestations and Virus Detection in the Ocular Surface of Adult COVID-19 Patients: A Meta-Analysis. (24th June 2021) - Chen, Yu-Yen; Yen, Yung-Feng; Huang, Li-Ying; Chou, Pesus
Abstract : Purpose . This study aims to examine the prevalence rate of ocular manifestations and the positive rate for the real-time reverse transcriptase-polymerase chain reaction (RT-PCR) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in conjunctival/tear swabs among adult patients with coronavirus disease 2019 (COVID-19). Methods . PubMed and EMBASE were reviewed between December 1, 2019, and January 31, 2021, and only peer-reviewed clinical studies in our pooled analyses were included. Details regarding the patient numbers, demographics, ocular manifestations, positivity of ocular surface RT-PCR, and severity of pneumonia were recorded from each study. Primary outcomes were the occurrence of ocular manifestations and virus detection on the ocular surface. Meanwhile, secondary outcomes included frequencies of various ocular symptoms/signs (s/s), the proportion of patients with ocular manifestation as the initial symptom, and the relationship between the severity of pneumonia and the presentation of ocular manifestations. Results . In total, 35 studies with 4, 432 adult COVID-19 patients were included in this analysis. The overall prevalence rate of ocular manifestations was found to be 11.3%, and the positive rate of SARS-CoV-2 in the ocular surface was 7.4%. The four most common ocular s/s were follicular conjunctivitis, redness, watering, and discharge. A proportion of 3.3% presented with ocular s/s preceding other findings. Besides, patients with higher severity of pneumonia were more likely to have ocular manifestations (odds ratio = 2.25; 95% confidence interval (CI): 1.45–3.50). Conclusion . As per our findings, it was determined that ocular transmission of SARS-CoV-2 might be possible, highlighting the importance of eye protective equipment among healthcare personnel.